2015
DOI: 10.5194/acp-15-1995-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sources of humic-like substances in the Pearl River Delta, China: positive matrix factorization analysis of PM<sup>2.5</sup> major components and source markers

Abstract: Abstract. Humic-like substances (HULIS), the hydrophobic part of water-soluble organic carbon (WSOC), account for a significant fraction of PM 2.5 mass. Their source studies are so far largely qualitative. In this study, HULIS and WSOC were determined in 100 PM 2.5 samples collected in 2009 at an urban site (Guangzhou) and a suburban site (Nansha) in the Pearl River Delta in South China. The annual average concentration of HULIS was 4.83 and 4.71 µg m −3 , constituting 8.5 and 10.2 % of the PM 2.5 mass, while … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(52 citation statements)
references
References 69 publications
(88 reference statements)
1
45
4
Order By: Relevance
“…DG (22°57′ 44.85″N, 113°44′39.36″E) is on a small hill (foothill of about 10 m) in the grounds of a sprawling botanical garden surrounded by scattered urban towns (~6 km). NS (22°45′08.90″N, 113°36′09.17″E) is located on top of a five-story building (~20 m agl) in Nansha Information Technology Park in Nansha District, south of Guangzhou urban areas and~15 km north of a shipping port [Kuang et al, 2015]. Journal of Geophysical Research: Atmospheres 10.1002/2016JD025315 PM 2.5 samples were collected at each site once every 6 days from 2011 to 2012, except for two intensive sampling periods, one in mid-November to December 2011 at NS and the other in mid-July to mid-August 2012 at GZ and NS, which sampled once every 2 days.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…DG (22°57′ 44.85″N, 113°44′39.36″E) is on a small hill (foothill of about 10 m) in the grounds of a sprawling botanical garden surrounded by scattered urban towns (~6 km). NS (22°45′08.90″N, 113°36′09.17″E) is located on top of a five-story building (~20 m agl) in Nansha Information Technology Park in Nansha District, south of Guangzhou urban areas and~15 km north of a shipping port [Kuang et al, 2015]. Journal of Geophysical Research: Atmospheres 10.1002/2016JD025315 PM 2.5 samples were collected at each site once every 6 days from 2011 to 2012, except for two intensive sampling periods, one in mid-November to December 2011 at NS and the other in mid-July to mid-August 2012 at GZ and NS, which sampled once every 2 days.…”
Section: Sampling Sitesmentioning
confidence: 99%
“…(14), sugars -which include levoglucosan, mannosan, and galactosan -are used as a tracer to derive SWSOC based on the primary ratio (5.28, Fig. S22) obtained from a biomass burning source profile measured in the PRD region (Lin et al, 2010). The relationship between SWSOC and SOC is examined in Fig.…”
Section: Implications For Secondary Oc (Soc) Estimationmentioning
confidence: 99%
“…Kuang et al (2015) also found that ship emissions could be a major source of secondary sulfate in the PRD in summer. HS and MDS had significantly higher concentrations than their upwind site, DM, suggesting that the area between MDS and HS could be a high-SO 2 -emission area, which is consistent with the fact that this area is an intensive industrial area.…”
Section: Identification Of High-emission Areas In the Prd Inmentioning
confidence: 99%